Autobiographical writing by early modern Hispanic women - Howe, Elizabeth Teresa, 1945- (Women and gender in the early modern world., 2015)
Women's life writing in general has too often been ignored, dismissed, or relegated to a separate category in those few studies of the genre that include it. The present work addresses these issues and offers a countervailing argument that focuses on the contributions of women writers to the study of autobiography in Spanish during the early modern period, both in Spain and in Mexico.